The Effect Of Indonesia’s 2024 General Election On The Abnormal Return And Trading Volume Activity Of Infrastructure Sector Stocks Listed On The Idx - Nur Hanifah; Pusposari, Devy (Telaah Ilmiah Akuntansi dan Perpajakan, 2025)
This study identifies whether there are differences in the Average Abnormal Return and Average Trading Volume Activity before and after the 2024 presidential and legislative elections in Indonesia. The study includes samples of infrastructure companies listed on the Indonesia Stock Exchange during February 2024 and analyzes the data utilizing the Wilcoxon signed-rank test. Based on signalling theory, general elections can inform investors and affect investment decisions. However, the results of the study exhibit no significant difference yet align more with the semi-strong form of the efficient market hypothesis, where stock prices reflect all publicly available information, including expectations of government policies that impact the market. This finding also reflects the precautionary motive of investors, where market participants anticipate political uncertainty by adjusting their investment strategies before the 2024 election. This indicates that political factors affect market sentiment but do not necessarily lead to significant volatility.